2005
DOI: 10.1159/000085126
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Type 2 Diabetes mellitus Causes Myocardial Dysfunction That Becomes Worse in the Presence of Cardiovascular Diseases: Results of the Myocardial Doppler in Diabetes (MYDID) Study 1

Abstract: Aims: Patients with type 2 diabetes mellitus (DM) often suffer disproportionately and have a worse outcome when burdened with cardiovascular complications compared with those without DM. A specific heart muscle disease reportedly caused by DM per se may explain this. We sought to investigate whether an echo Doppler diagnosis of such a myocardial disease is clinically relevant in DM with or without coexistent coronary artery disease (CAD) and/or hypertension (HTN). Subjects andMethods: Two hundred subjects (127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…A PC-based version of STATISTICA version 6.0 was used for data analyses. Intra-observer variation was similar to our previous study [ 11 ]. All continuous variables are expressed as mean ± SD.…”
Section: Methodssupporting
confidence: 90%
“…A PC-based version of STATISTICA version 6.0 was used for data analyses. Intra-observer variation was similar to our previous study [ 11 ]. All continuous variables are expressed as mean ± SD.…”
Section: Methodssupporting
confidence: 90%
“…Although it is difficult to clinically identify whether hyperglycemia is associated with myocardiac dysfunction in patients with DM, recent echocardiographic studies have shown that correlations exist between the state of glycemic control and ventricular function. Recent studies involving adult patients with type 2 DM showed that hyperglycemia influences on LV systolic function, especially with respect to ventricular long axis function 18)19). A study using magnetic resonance imaging indicates that there is a correlation between hyperglycemia and LV function in type 1 DM as well 20).…”
Section: Discussionmentioning
confidence: 99%
“…Since left ventricular (LV) structure and function might be altered in type 2 diabetes even in the absence of cardiovascular disease, presence of coexistent microalbuminuria in DM may be an early marker of or contribute to more severe LV dysfunctions. Previous studies from our group have suggested that uncomplicated DM may decrease LV myocardial functional reserve, which could be further compromised when associated with systemic arterial hypertension (HTN) or coronary artery disease (CAD) or their combination (2,3). Also shown is the independent association in non-diabetics between MA and surface electrocardiogram (ECG) showing ischemic abnormalities, suggesting that MA has additional value to conventional risk indicators in predicting cardiovascular disease (4).…”
mentioning
confidence: 89%